Methicillin-resistant staphylococcus aureus in milk from dairy cows with chronic mastitis - Hayriye Yeşim Can; Mehmet Elmalı; Yaşar Ergün (Eurasian Journal of Veterinary Sciences)
Aim: The aims of this study were: i) to isolate coagulase positive Staphylococcus (CPS) and coagulase-negative Staphylococcus (CNS) in milk from dairy cows with chronic recurrent mastitis, ii) to verify isolates in terms of Staphylococcus spp., Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA) by multiplex PCR, and iii) to determine the antimicrobial susceptibility of the isolates by disk diffusion method. Materials and Methods: A total of 52 milk samples were collected from the dairy cows with chronic recurrent mastitis in Hatay province. Isolation and identification of CPS and CNS were detected by using classical culture method. All CPS and CNS isolates were investigated for antimicrobial susceptibility and also, were confirmed as Staphylococcus spp., S. aureus and MRSA by multiplex PCR based on 16S rRNA, nuc, and mecA gene sequences, respectively. Results: Positive results were found in 48.0% of the milk samp-les. A total of 56 Staphylococcus spp. isolates (22 CPS and 34 CNS) were obtained from the positive samples. Twenty (90.9%) of the CPS isolates were detected as S. aureus. The mecA gene was detected in 18 (90%) of the S. aureus isolates. By disk dif-fusion method, resistance to erythromycin (66%), tetracycli-ne (62.5%), ampicillin (60.7%), penicillin (60.7%), cefoxitin (50%), oxacillin (46.4%), and chloramphenicol (5.3%) was also determined in this study. Conclusion: In the study, the detection of antibiotic resistant Staphylococcus strains and especially MRSA in milk from dairy cows with chronic recurrent mastitis should be taken into account for potential spread through the dairy food chain.